2005
DOI: 10.5650/jos.54.203
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Production of Liquid Wax Ester by Immobilized Lipase

Abstract: Oleyl oleate, a liquid wax ester was synthesized by an immobilized Candida antartica lipase B (Novozym 435) as biocatalyst using oleic acid and oleyl alcohol. The effects of various reaction parameters were optimized to obtain a high yield of liquid wax esters. Investigation in large scale production was performed in batch mode of stirred tank reactor (STR) with one multi-bladed impeller. The optimum condition to produce liquid wax ester was, reaction time (RT); 30 min, temperature (T); 50 , amount of enzyme (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…[29] As the reaction proceeded, the substrate concentration decreased, which consequently reduced the degree of saturation of the enzyme with the substrate. [30] It can be seen that the percentage yield increased slightly with the increasing of the solvent hydrophobicity (log P) up to 6 h. The observed increase in yield was attributed to the activity of the enzyme, which was affected by the polarity of the employed organic solvent. [31] Corroborating previous reports has shown that solvent with a higher log P had a better rate of esterification.…”
Section: Resultsmentioning
confidence: 99%
“…[29] As the reaction proceeded, the substrate concentration decreased, which consequently reduced the degree of saturation of the enzyme with the substrate. [30] It can be seen that the percentage yield increased slightly with the increasing of the solvent hydrophobicity (log P) up to 6 h. The observed increase in yield was attributed to the activity of the enzyme, which was affected by the polarity of the employed organic solvent. [31] Corroborating previous reports has shown that solvent with a higher log P had a better rate of esterification.…”
Section: Resultsmentioning
confidence: 99%
“…Among of the works are syntheses of esters from palm oil. Alcoholysis of triglycerides from palm oil to produce palm oil esters using lipase as a catalyst is a relatively simple process and moreover the starting materials are cheap [3][4][5][6] . Synthesis or modification of lipids for example; modification of Palm Oil into Palm Oil Esters (POEs) has grown due to the possibility of obtaining a wide variety of high quality natural products under mild reaction conditions utilizing selective enzyme substrate as environment friendly biocatalysts 2,7) .…”
Section: Introductionmentioning
confidence: 99%
“…High performance enzymatic synthesis of a liquid wax ester using immobilized lipase from C. antartica has been previously reported by Radzi et al 9) and the optimized reaction conditions was achieved through response surface methodology 10) . The high conversion and productivity of wax ester was further studied in large scale production using batch mode stirred tank reactor with one-multi bladed impeller 11) .…”
Section: Introductionmentioning
confidence: 99%